Stability Analysis of Axially Functionally Graded Beams Using the Differential Quadrature Method (Advances in Applied Mathematics and Mechanics, 2024)
This paper investigates the critical buckling behavior of axially functionally graded (FG) material beams with three end support conditions. The FG materials are assumed to have continuously graded based on a power-law function of thevolume fractions of the constituents. The governing equation for buckling is derivedand solved using the differential quadrature (DQ) method. A comparison betweenthe results obtained from the DQ method and the analytical approach reveals excellent agreement. The effects of various parameters, such as the gradient index andboundary conditions, on the critical buckling load is thoroughly analyzed. The findings highlight the efficiency and accuracy of the DQ method for analyzing functionallygraded beams. Moreover, the insights gained from this study can inform the designand optimization of functionally graded structures.